Cost-effectiveness of rapid diagnostic tests, compared to microscopic tests, for the diagnosis and treatment of gestational malaria in Colombia from an institutional perspective (2020)
ABSTRACT : Background: Gestational malaria is associated with negative outcomes in maternal and gestational health; timely diagnosis is crucial to avoid complications. However, the limited infrastructure, equipment, test reagents, and trained staf make it difcult to use thick blood smear tests in rural areas, where rapid testing could be a viable alternative. The purpose of this study was to estimate the cost-efectiveness of rapid tests type III (Plasmodium falciparum/Plasmodium spp P.f/pan) versus microscopic tests for the diagnosis and treatment of gestational malaria in Colombia. Methods: Cost-efectiveness analyses of gestational malaria diagnosis from an institutional perspective using a decision tree. Standard costing was performed for the identifcation, measurement and assessment phases, with data from Colombian tarif manuals. The data was collected from Health Situation Analysis, SIVIGILA and meta-analysis. Average and incremental cost-efectiveness ratio were estimated. The uncertainty was assessed through probabilistic sensitivity analysis. Results: The cost of rapid diagnostic tests in 3,000 pregnant women with malaria was US$66,936 and 1,182 disability adjusted life years (DALYs) were estimated. The cost using thick blood smear tests was US$50,838 and 1,023 DALYs, for an incremental cost-efectiveness of US$ 101.2. The probabilistic sensitivity analysis of rapid diagnostic tests deter mined that they are highly cost-efective in 70% of the cases, even below the US$1,200 threshold; also, they showed an incremental net monetary beneft of $150,000 when payer’s willingness is US$1,000. Conclusion: The use of rapid diagnostic tests for timely diagnosis and treatment of gestational malaria is a highly cost-efective strategy in Colombia, with uncertainty analyses supporting the robustness of this conclusion and the increased net monetary beneft that the health system would obtain. This strategy may help in preventing the nega tive efects on maternal health and the neonate at a low cost.